The Use of Song to Activate Students' Critical Thinking Skills - Rachmawati Achadiyah; Muhammad Ulul Azmi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
Previous research has demonstrated the great success of the use of song in teaching listening skills integrated with critical thinking skills. Myriad research has examined the role and the benefits of songs in ELT with monotonous activities. Therefore the study is conducted to bring new insights into it. Five English teachers with more than seven years of teaching experience and have completed teaching critical thinking trainees were selected as the research participants. Since an observational fieldnote was used to obtain the data this study employed a case study as the design. This study discussed the teaching steps of teaching listening skills which used the song as the main material integrated with critical thinking. Several ways revealed by the teacher to activate students’ critical thinking are providing critical questions related to the content of the song and stimulating students constantly to eager them to answer critically. Several strategies adopted by these teachers include: highlighting several words and asking about the meaning, connecting to students' real-world settings, assigning them to make a judgment, and examining the current situation and conditions, These five teachers applied a higher-order thinking style to their teaching and have effectively activated and guided students to think critically.